Collection of Land & Building Rights Acquisition Fees (BPHTB) based on Transaction Price in Land & Building Sales-Purchases in Batang Regency - Apri Yahya, Muhammad; Ispriyarso, Budi (Universitas Islam Sultan Agung, 2025)
Collection of Land and Building Acquisition Tax (BPHTB) is required to obtain land and building rights, it is mandatory to pay BPHTB tax. Therefore, a thesis was compiled with the title